Development and validation of a novel IoT-enabled electrical resistance system for non-destructive monitoring of atmospheric corrosion in steel structures - Komary, Mahyad; Komarizadehasl, Seyedmilad; Tošić, Nikola; Turmo, Jose (Građevinski materijali i konstrukcije, 2025)
Effective corrosion monitoring in steel structures is crucial for sustainability and safety. Traditional electrochemical techniques, while common, are complex, require technician presence, and often lack accuracy in on-site quantification of corrosion rates and metal thickness loss. Additionally, these systems are costly, typically restricting their use to high-budget Structural Health Monitoring (SHM) projects and leaving conventional structures, such as steel bridges, without adequate monitoring. To address this gap, this paper introduces LEROY (Low-cost Electrical Resistance Ohm Analyzer), an Arduino-based, Internet of Things (IoT)-enabled device designed as a low-cost Data Acquisition (DAQ) system for atmospheric corrosion monitoring (ACM) of steel structures. LEROY achieves high resolution in the milliohm range and stable electrical resistance (ER) measurements, providing a novel solution for non-destructive testing (NDT). Validated through tests on known resistors and steel samples (AISI 304HN and AISI 1010), LEROY demonstrated high accuracy, with a maximum relative difference of 0.59% compared to a commercial resistance meter. A six-month accelerated corrosion test further confirmed its ability to track corrosion progression in metal thickness loss and provide real-time updates on relative corrosion rates. Combining wireless data streaming with affordability, LEROY supports SHM applications in budget-constrained infrastructure projects, enhancing the maintenance and safety of steel structures.